EVALUATION OF TEMPE LAKE MANAGEMENT POLICIES IN WAJO REGENCY, INDONESIA - Andi Rewo Batari Wanti; Juanda Nawawi (International Conference on Social and Islamic Studies, 2021)
Lake Tempe is one of the 15 lakes in critical condition in Indonesia. It is located in South Sulawesi province, bordering the Wajo Regency, Soppeng Regency, and Sidrap Regency. However, the tempe lake management policy in the form of a regional regulation has been only owned by the government of Wajo Regency. This study uses qualitative research that utilize the William N Dunn model of policy evaluation. The management of Lake Tempe tends to base on the Pentahelix concept framework, which has been involving the local government of Wajo Regency, State Enterprises/Private Sectors, Universities/Academics, Media, Community/Non-Governmental Organizations. Besides, it refers to the program of the Ministry of Environment, namely Gerakan Penyelamatan Danau (Lake Rescue Movement). The criticism of the Lake Tempe Management Policy in Wajo Regency is that the content of the policy analysis only focuses on ecosystem issues, while the policy should include several important aspects, such as the social, economic, and cultural fields of the Lake Tempe coastal community. Then a synergistic multi-sectoral policy is needed.